VD_FINDINFO LAVAM 24/10 - 3/2011 vom 28. Dezember 2010 - VD Tribunal cantonal (2010)
PRESTATION D'ASSISTANCE, REVENU DÉTERMINANT, PRIME D'ASSURANCE-MALADIE | 11 al. 1 LVLAMal, 12 al. 1 LVLAMal, 9 LVLAMal, 23 al. 2 RLVLAMal